Rhetorical Moves and Meta-discourse Markers in Abstracts of Indonesian Scopus Indexed Journals Across Academic Disciplines - Dwi Indarti (Journal of Languages and Language Teaching, 2022)
Rhetorical moves purposes to examine the basic structures of research articles, while meta discourse markers are elements to construct and to establish ideas and arguments. This study compares rhetorical moves and the function of meta discourse markers in research articles abstracts of different academic disciplines published in reputable indexed journals. This study employs (Pho, 2008)’s five-move analysis and the classification of meta discourse marker proposed by (Dafouz-Milne, 2008) as the research framework. The writer took five Indonesian Scopus Q1 and Q2 indexed journals from different academic disciplines. Those are Indonesian Journal Science and Technology (IJoST), Indonesian Journal of Applied Linguistics (IJAL), Journal on Mathematics and Education (JME), Studia Islamika and Forest and Society.  The results show that in terms of rhetorical move of abstracts, M2 and M4 became the moves which occur in all journal abstracts. In terms of meta discourse markers, all journal abstracts employ logical markers and code glosses. Sequencers, topicalisers, and illocutionary markers are used in small numbers, while reminders and announcements are not be found in any abstracts. The findings could help students and writers to produce abstracts that fulfill the requirements to be published in Scopus indexed journals.